Hemochromatosis Mistakenly Treated as Rheumatoid Arthritis - Akgol, Gurkan; Ulusoy, Hasan; Kamanli, Ayhan (Turkish League Against Rheumatism, 2014)
A 44-year-old female patient was admitted to our clinic with complaints of episodic pain, swelling attacks, and progressive deformity in both wrists and metacarpophalangeal joints lasting for five years. Based on her complaints, she had been diagnosed with rheumatoid arthritis and taken methotrexate, sulphasalazine, and prednisolone for two years, however, the patient had discontinued her treatment a year earlier due to ongoing symptoms. Physical examination revealed limited range of motion of both wrists and flexion deformity of the fingers without active inflammation signs. Hand X-ray showed typical signs of osteoarthritis characterized by narrowed joint spaces, subchondral sclerosis, and cyst formation. The distal and proximal interphalangeal joints were markedly preserved, and there were large, hook-like osteophytes in the heads of the metacarpal bones, indicating a typical presentation of hemochromatosis. Laboratory tests revealed that the erythrocyte sedimentation rate and C-reactive protein and uric acid levels were within the normal range, and the antibody tests were negative for rheumatoid factor, anti-nuclear antibodies, and anti-cyclic citrullinated peptides. Although the serum iron and ferritin levels were normal, there was a high transferrin saturation rate. Magnetic resonance imaging demonstrated a hepatic iron concentration of 44 mu mol/g (reference: <36 mu mol/g). Genetic studies showed homozygous for the H63D mutation. Based on these findings, the patient was diagnosed with hereditary hemochromatosis and scheduled for follow-up visits. In conclusion, hemochromatosis should be considered in the differential diagnosis in patients suffering from slow-progressing arthritis with chronic deformity.
Keywords: Hemochromatosis; osteoarthritis; radiology; rheumatoid arthritis